Effects of aging on experimentally induced pain perception during a distraction task - Francisco G. Fernández-Palacios; Angela Tejera-Alonso; Juan C. Pacho-Hernández; Arvin Naeimi; Ana I. de-la-Llave-Rincón; Silvia Ambite-Quesada; Ricardo Ortega-Santiago; César Fernández-de-las-Peñas; Juan A. Valera-Calero; Margarita Cigarán-Mendez (Scientific Reports)
Abstract To investigate the effects of psychological (anxiety, depression, pain catastrophizing) aspects, pain sensitivity, cognitive performance and executive functions, on pain perception during a distraction task in an acute pain laboratory in young and elderly adults. Twenty-six young (age: 20.0 ± 1.6 years) and thirty-three elderly (age: 68.0 ± 3.8 years) adults completed four self-reported questionnaires (Hospital Anxiety and Depression Scale—HADS, Pain Anxiety Symptoms Scale-20—PASS/20, Pain Catastrophizing Scale—PCS, and Pittsburgh Sleep Quality Index—PSQI), pressure pain thresholds (PPTs), a battery of executive functions (working memory, cognitive flexibility, mental inhibition), and attention levels before performing two distraction tasks (1-back, 2-back). Pain was experimentally induced with a thermal stimulus applied at the non-dominant forearm to provoke moderate pain (70/100 points) before and during the distraction tasks. Age (young, elderly), psychological and psychophysical variables, and neurocognitive test performance levels (low, medium, high) were included in separate ANCOVAs to compare pain intensity at baseline and during distraction tasks. All ANOVAs revealed a main effect of distraction task, indicating that perceived pain intensity scores were lower during both distraction tasks (p < 0.001) compared to baseline. Overall, there was no significant effect of age on perceived pain intensity after distraction tasks, except for an interaction effect between the distraction task and age group depending on PPTs levels (F [2,49] = 3.7, p = 0.03). Elderly adults (with higher PPTs) reported lower perceived pain intensity during both distraction tasks compared to younger adults (lower PPTs). This study found that the hypoalgesic effect of a distraction task is not directly associated with age or neurocognitive function and attention levels in pain-free subjects, but it was related with higher PPTs (lower pressure pain hyperalgesia).